Crack determination by crack tip diffraction technique / Maryam Husin - Husin, Maryam (2000)
The objective of this thesis is to investigate on a new technique of ultrasonic for measuring height of crack which is perpendicular and obliquely to the surface. Crack tip diffraction technique is used and it is the best method with regard to accurate sizing. This method differs from traditional pulse echo technique in that because it monitor diffracted signal at the edges of defect hence the position and size of defect can be measured accurately. This experiment was carried out by using three different types of probe angle that are 4 5°, 60° and 70°. The specimen have different positions of crack within the component, at the surface and at the bottom of the specimen. The length and the width of steel specimen are 150 mm and 25 mm respectively. The specimen were fabricate with different length of crack from 1 mm until 12 mm to in order to find the accuracy of this technique. From this experiment, probe angle of 60° is the best probe to for this technique due to it capabilities to detect crack in both position. During this experiment the instrument sensitivity (gain) need to set at high level, if not the no diffracted echo would display in the CRT screen. In practise, diffracted echoes at crack tip are not so clear, so it need experience personal to distinguish the relevant echoes. For sizing crack location at the bottom, the experimental value are close to the actual value and for sizing crack location at the surface the result shows that when size of a crack below than 5 mm the accurate reading cannot be obtained, it may be due to beam spread.